Qualidade de vida de cuidadores de crianças e adolescentes com condições crônicas - Cardoso, Érika Leite da Silva (2019)
Chronic conditions (CC) are health problems that require continuous management for an indeterminate period of time. It is known that in childhood and adolescence, CC does not only affect the child / adolescent, but the whole family. However, the primary caregiver is the most affected family member, since he needs to change his whole routine to devote himself to care. In this perspective, the present study aimed to evaluate the quality of life of caregivers of children and adolescents with chronic conditions registered in the Information System for Children of Adolescents with Chronic Diseases (SICADC). It is a research of the analytical type, descriptive-explanatory, of quantitative nature, with a cross-sectional design. Data for the development of the study were obtained through the SICADC. Currently, the system has 300 children and adolescents enrolled, as well as their respective caregivers. Of these, 20 adolescents were over 18 years of age and 18 children / adolescents died. Thus, an accessible population of 262 caregivers remained. Based on this quantitative, a sample calculation with a confidence level of 95% and an error of 5.5% was obtained, thus obtaining a sample of 143 caregivers, who were selected from a physical process of randomization. Data collection took place between August and October 2018 and occurred as follows: after selecting a caregiver registered in SICADC, the researcher contacted the application for the quality of life instrument, the World Health Organization Quality of Life, abbreviated version (WHOQOL-Bref). Subsequently, the results of this measurement were evaluated along with the information provided in the SICADC. For the analysis of the data, Descriptive Statistics, a Binary Logistic Regression model and the Decision Tree were used. As a result, in a WHOQOL Bref analysis, the total quality of life score of the caregivers obtained a median of 61. Among the domains of the instrument, the domains of environment and social relations were most affected. From the binary logistic regression it was possible to identify the variables that had an impact on the poor quality of life of the caregiver. The model identified as risk factors for this outcome: the highest number of children with chronic conditions, the routine use of medication by the caregiver and the financial limitation after diagnosis of the child / adolescent. On the other hand, the regression pointed out that owning a home and having emotional support are protective factors. In turn, the decision tree selected variables that were able to predict whether the caregiver presented high or low quality of life, are: the number of children with a chronic condition, whether the caregiver has any disease, family involvement in care, housing situation, emotional support and restrictions related to the diagnosis of the child / adolescent. Thus, the study brought unique and timely information that proves that not only the chronically ill child / adolescent deserves attention, but also his / her caregivers. In this way, knowing the factors that can affect their quality of life, will collaborate with the decision making of health professionals, making them provide a more consistent and targeted assistance to the real needs of this public.